Low-frequency electrical stimulation combined with preventative pelvic floor muscle exercises and knowledge-attitude-practice model in women with urinary retention after a pelvic surgery - Liu, Hong; Guo, Lixin; Kang, Zhichen; Zhang, Jiangchun; Liu, Zhongliang; Liu, Taiyuan; Liu, Wei; Qu, Fuling (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study was to explore the efficacy of low-frequency electrical stimulation (LFES) combined with preventative pelvic floor muscle exercises (PPFME) and knowledge-attitude-practice model (KAP model) in women with urinary retention (UR) after a pelvic surgery and the effect on quality of life (QOL). The clinical data of 153 women hospitalized with UR after a pelvic surgery from January 2015 to June 2019 were retrospectively analyzed and divided into the Control Group (CG, n=45, LFES+PPFME) and the Study Group (SG, n=108, LFES+PPFME+KAP model) according to the different treatment methods. Following indicators were compared between the two groups: clinical efficacy, time to first urination, urine output, rate of extubation in 3D, rate of repeated intubation, urodynamic indicators before and after treatment, postvoid residual (PVR), bladder compliance (BC), maximal flow rate (Q-max), pressure of detrusor at Pdet-Q-max (Pdet-Q-max), changes in QOL, incidence of urinary tract infection, and length of stay (LOS). Compared to CG, SG showed higher overall response rate (ORR) and rate of extubation in 3D, shorter time to first urination, higher urine output, lower rate of repeated intubation and incidence of urinary tract infection, and shorter LOS (P<0.05); both groups achieved improvements in urodynamic indicators and QOL score after treatment (P<0.05); the urodynamic indicators and QOL score in SG were better than the CG’s (P<0.05). LFES combined with PPFME and KAP model is effective in treating women with UR after a pelvic surgery by efficaciously improving patients’ urination and QOL.